Cultural studies : from theory to action - Leistyna, Pepi; Leistyna, Pepi (Malden, MA : Blackwell Pub., 2005)
""Cultural Studies: From Theory to Action is a landmark collection of key works that inspires conversations about issues of social and economic justice and the current crisis in democracy."" ""In addition to a substantial essay that frames the project, this valuable resource includes generous lists of suggested readings, activist organizations, web resources, and journals that ""go against the grain."" These are all designed to continue the conversation that the anthology begins, and to enable readers to get involved in their own communities and coalitions.""--Jacket
Unity and changes in the ideology of political economy / S. Amin -- The postcolonial aura: Third World criticism in the age of global capitalism / Arif Dirlik -- Time and class / Zygmunt Bauman -- Theoretical therapies, remote remedies: SAPs and the political ecology of poverty and health in Africa / Brooke G. Schoepf, Claude Schoepf & Joyce V. Millen -- A new way of thinking in action: the Zapatistas in Mexico-- a postmodern guerrilla movement? / Fernanda Navarro -- Workers' resistance / Anita Chan -- Life against gold / Ustun Reinart -- The campus anti-sweatshop movement / Richard Apelbaum & Peter Dreier -- The NGO-ization of grassroots politics / Sangeeta Kamat -- Global media, neoliberalism, and imperialism / Robert McChesney -- Theoretical orthodoxies: textualism, constructivism and the 'new ethnography' in cultural studies / David Morley -- Disney, Southern Baptists, & children's culture: the Magic Kingdom as Sodom and Gomorrah? / Henry Giroux -- Seeing ourselves, being ourselves: broadcasting Aboriginal television in Canada / Jennifer David -- Zines / Stephen Duncombe -- The Ho'okele netwarriors in the liquid continent / Kekula P. Bray-Crawford -- Internet subcultures and political activism / Richard Kahn & Douglas Kellner -- Staring back: self-representations of disabled performance artists / Rosemarie Garland Thomson -- Noise from underground: punk rock's anarchic rhythms spur a new generation to political activism / Johnny Temple -- Rethinking recognition / Nancy Fraser -- The roots of international racism / Fidel Castro -- Invention, memory, and place / Edward Said -- White ethnic unconsciousness / Pepi Leistyna -- Racial justice in a multi-ethnic society / Bhikhu Parekh -- Where was the color in Seattle? looking for reasons why the great battle was so white / Elizabeth 'Betita' Martinez -- Sharing the story of the movement: the Project Hip-Hop experience / Nancy Murray -- World Conference against Racism: prospects and challenges / A.S. Narang -- Women workers and capitalist scripts: ideologies of domination, common interests, and the politics of solidarity / Chandra Talpade Mohanty -- Radicalizing feminism from the 'movement era' on / Joy James -- Mana wahine theory: creating space for Maori women's theories / Leonie Pihama -- Afghan women's long struggle: women working for freedom / Tahmeena Faryal -- Minjung feminism: Korean women's movement for gender and class liberation / Miriam Ching Yoon Louie -- Reconstructing masculinity in the locker room: the Mentors in Violence Prevention Project / Jackson Katz -- The globalization of sexual identities / Dennis Altman -- Black lesbians: passing, stereotypes and transformation / Jewelle Gomez -- Trashing the clinic and burning down the beauty parlor: activism transmutes pitiable patients into feisty gender radicals / Pat Califia -- At a turning point: organized labor, sexual diversity, and the new South Africa / Mazibuko K. Jara, Naomi Webster, and Gerald Hunt -- Gay teens fight back: a new generation of gay youth won't tolerate harassment in their schools / Doug Ireland
Includes bibliographical references (pages 520-554) and index
Keywords: Culture -- Study and teaching -- Political aspects; Social justice; Social movements; Aufsatzsammlung